KAJIAN MATERI SEJARAH KEBUDAYAAN ISLAM DALAM KITAB AL-BARZANJI DAN IMPLIKASINYA DALAM PEMBELAJARAN PAI - Saputra, Dwi Wahyu; W, Dhevin M.Q Agus Puspita (STKIP Pesisir Selatan, 2025)
With education, humans will gain progress and developments in themselves so that they become qualified and qualified humans. This study aims to examine the content of Islamic Cultural History material in the Al-Barzanji Book and its implications in learning Islamic Religious Education (PAI). The A-Barzanji Book is a classic religious literary work that contains the biography of the Prophet Muhammad SAW in the form of prose and poetry, and is rich in values ​​of faith, morals, and spirituality. This study uses a qualitative approach with a literature study method. The results of the study indicate that Al-Barzanji has great potential as a source of PAI and SKI learning because it can integrate students' cognitive and affective dimensions. The poems contained in this book are able to arouse emotions and shape religious character through the Prophet's example. However, its use in learning is still limited due to the lack of teacher understanding and limited teaching media. Therefore, teacher training and the development of Al-Barzanji-based teaching tools are needed so that this book can be integrated contextually into the PAI curriculum. Al-Barzanji can be an effective medium in forming students who are faithful, devout and have noble character.